The gene expression profile of the glucocorticoid receptor 1 (gr1) but not gr2 is modulated in mucosal tissues of gilthead sea bream (Sparus aurata) exposed to acute air-exposure stress - Vallejos-Vidal, Eva; Sanz-Milián, Beatriz; Teles, Mariana; Reyes-Cerpa, Sebastián; Mancera, Juan Miguel; Tort, Lluis; Reyes-López, Felipe E. (Frontiers in Marine Science, 2022)
The perception of an acute stressor (short-duration; high-intensity) induces a physiological response that activates the hypothalamic-pituitary-interrenal (HPI) axis and the subsequent release of cortisol. Cortisol carries out its effect at the molecular level through its recognition by the mineralocorticoid receptor (MR) and the glucocorticoid receptor (GR). Recently, we unveiled the nucleotide sequence of the glucocorticoid receptor 1 (gr1) and gr2 in gilthead sea bream (Sparus aurata). Importantly, GR1 and GR2 respond to different levels of cortisol concentration in fish and, consequently, play a differential role in the stress response. To date, and despite their relevance, no data describes the modulation of these receptors in response to an acute stressor in gilthead sea bream (S. aurata). In this study, we evaluated the kinetics of modulation of cortisol receptors expression (gr1, gr2, mr), and its similarity with the expression pattern of selected genes associated with stress (hsp70; enolase) and immune response (lysozyme; c3; il-1β; tnf-α; il-10; tgf-β1) in gilthead sea bream mucosal tissues (skin; gills; anterior gut). To do it, fish were acutely stressed by three-minute air exposure, and the expression profile was evaluated at zero, 1 h, 6 h, and 24 h post-stress (hps). The cortisol level in plasma and skin mucus peaked at 1 hps. All the mucosal tissues showed a time-dependent and tissue-specific upregulation of gr1 and mr. The immune-related genes showed the upregulation of il-1β at 6 hps (gills; anterior gut), and tnf-α and c3 at 24 hps (anterior gut). Taking together, our study concludes that fish subjected to three-minute air exposure modulated the expression of gr1 but not gr2 in mucosal tissues (skin; gills; anterior gut). Furthermore, our data reinforce the idea of a stimulatory effect induced in genes associated with the innate immune response after acute stress but focused at the mucosal level and in a time- and tissue-dependent manner.